Low-cost portable system for measurement and representation of 3D kinematic parameters in sport monitoring: discus throwing as a case study - Navarro-Iribarne, J. F.; Moreno-Salinas, D.; Sánchez-Moreno, J. (Sensors, 2022)
Monitoring of sports practice has become an almost essential tool in high-level professional training. The knowledge of the exact movements performed by an athlete provides a great advantage over conventional training, since the best performance can be theoretically known in advance and the trainer will expect the real athlete`s movements to approximate it. Following this trend, this article deals with the design and development of a low-cost wearable biofeedback system for the measurement and representation of kinematic parameters in 3D. To capture the athlete`s movements, an inertial measurement unit (IMU) is used, whose data are processed in an microcontroller-based architecture. The kinematic parameters of the athlete`s movement are sent via Bluetooth to a smart phone, where they are displayed graphically. Experimental examples show the effectiveness of the device developed and illustrate the key results derived.